2021
DOI: 10.1037/tep0000316
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with passing the EPPP on first attempt: Findings from a mixed methods survey of recent test takers.

Abstract: Licensure as a psychologist in the United States and Canada depends in part on passing the Examination for Professional Practice in Psychology (EPPP). The current study examines the quantitative relationship between demographic and training characteristics on EPPP first-time pass rate and provides qualitative data that speaks to viable approaches to better prepare future test-takers. A survey was administered in 2018 to a sample of 1,691 early career members (i.e., earned their doctorate in the last 10 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Clinical psychology law is a burgeoning field, with more and more students seeking related training (DeMatteo et al, 2019). Generally speaking, internship placement is associated with career mobility and success (e.g., Macura & Ameen, 2021), and forensic/ correctional psychology is no exception (Malesky & Proctor, 2012). Yet, while the field has grown, applicants lack updated guidance on "what it takes" to acquire internships with forensic and/or correctional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical psychology law is a burgeoning field, with more and more students seeking related training (DeMatteo et al, 2019). Generally speaking, internship placement is associated with career mobility and success (e.g., Macura & Ameen, 2021), and forensic/ correctional psychology is no exception (Malesky & Proctor, 2012). Yet, while the field has grown, applicants lack updated guidance on "what it takes" to acquire internships with forensic and/or correctional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based interventions that address multiple dimensions of wellness are needed for those without mental health diagnoses (Payne, 2017; Young, 2004); interventions are needed to address implicit racism inherent in health care systems, agencies, and organizations (Blume, 2016); practitioners often lack competence and confidence in addressing race and racism in clinical encounters (Buchanan & Wiklund, 2020; Estaban & Battle, 2003); there is a need for greater accessibility of clinical services to populations that fall through the cracks where financial structures disincentivize care for individuals from lower and middle SES communities and people of color, and the need exists for equitable and sustainable health care reimbursement (Palozzi et al, 2020); psychological assessment does not adequately capture culturally responsive constructs central to health equity work (Braveman, 2006); and the Examination for Professional Practice in Psychology may have an impact that is counter to the goal of achieving a diverse practice workforce (Macura & Ameen, 2021);…”
Section: Apa Presidential Task Force On Psychology and Health Equitymentioning
confidence: 99%
“…In a replication study, Sharpless (2021) subsequently drew data from a different state and found that White and Asian applicants passed more frequently on their first attempt than did either Black or Hispanic applicants (Sharpless, 2021). Another report the same year by a different investigative team tapped a diverse national sample and again found that White candidates were more likely to pass on their first attempt (Macura & Ameen, 2021).…”
mentioning
confidence: 99%